Sierra Leone’s Radio Teaching Programme : Challenges and Opportunities - Gutierrez Bernal, Marcela (World Bank, Washington, DC, 2021)
Radio has been a critical tool to ensure the continuity of learning in the face external shocks. Sierra Leone has used this tool both when Ebola struck, and now, with COVID-19. What can we learn from their experience what can be done to improve the program and deepen its impacts This report documents the experience of Sierra Leone using radio as an emergency response and its plans for the future. It also presents emerging evidence of the impact of radio over learning using information from Sierra Leone and globally. It provides recommendations including using radio as remediation tool to complement normal schooling. using radio to improve learning during school hours, and using radio as a continuous professional development tool.